Determinan Total Aset Bank Pembiayaan Rakyat Syariah (BPRS) di Pulau Jawa Tahun 2014 - Anton Sudrajat (Islamic Economics Journal, 2015)
To create a strong BPR Sharia in Java Island needs to be supportedby significant asset growth so as to increase confidence of society to BPRSharia. The purpose of this research is to examine the influence of financing,DPK, Financing to Deposit Ratio, and Non Performing Financing to totalasset of BPR Sharia in Java Island consisting of DKI Jakarta, West Java,Banten, Central Java, D.I.Yogyakarta, and East Java. The result shows thatfinancing, Third-part fund (DPK), Financing to Deposit Ratio (FDR), andnon Performing Financing (NPF) simultaneously has significant effects tothe total assets of BPR Sharia in Java. While partially, only financing hassignificant influence to total assets of BPR Sharia in Java.